Comparative study of intravenous oxytocin and intra-umbilical vein oxytocin against intravenous oxytocin therapy during caesarian section. - Dewolage, M (My University, 2008)
Prospective randomized trial. Setting: Ward 17 Colombo South Teaching Hospital population: patients who were undergoing caesarian section at term (37weeks to 42week) from 28/12/2005 to 30/4/2006. All the patients who fulfill selection criteria were randomly allocated to two groups. Five units of oxytocin were given intravenously once baby was delivered completely. If the patient is selected to test group 5 iu of additional oxytocin dose was given to umbilical vessel close to its insertion once umbilical cord was clamped. If patient was selected to control group only 5iu of oxytocin was given intravenously once baby was completely delivered. Placental separation time was calculated and mean placental separation times were statistically compared. All together 87 patients are randomized to two groups. Forty. three subjects include in test group. Forty four subjects randomized into control group. Mean age of the test group is 28.09 years. Mean age of the control group was 31.27.Mean gravidity were 1.9 and 2.3 in test and control groups respectively. Mean parity was 0.88 and 1.32 in test and control groups respectively. Mean number of children were 0.72 and 0.98 in test and control groups respectively. Mean placental sepal'ation time of test group (Intravenous + Intra-umbilical vein) was 96.51s (SD